Prevalence and risk factors for extrinsic discoloration in deciduous dentition of Peruvian schoolchildren - Chumpitaz-Durand, Rubén Balabonce; Córdova-Sotomayor, Daniel Ángel (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: discoloration due to fluorosis is frequent in northern Peru, making extrinsic discoloration to go unnoticed or confused with other conditions due to lack of appropriate differential diagnosis. The aim of this study was to determine the prevalence and risk factors associated with extrinsic discoloration in deciduous dentition among schoolchildren of primary schools from Pimentel, Salas, and Chiclayo (Lambayeque, Peru) in 2015. Methods: This was an epidemiological analytical study using cases and controls, aimed at identifying risk factors associated with extrinsic discoloration. It used a census population of 238 clinical records of first and second graders from three different primary schools. Calibration was conducted by differential diagnosis of discoloration (kappa k = 0.76), using Odds Ratio (OR) as a measure of association to determine the significance of risk factors. Results: The prevalence of extrinsic discolorations was 6.72%. In all three schools there was significant association between low presence of caries and extrinsic discoloration, like this: Nicolás La Torre (OR: 23.46 CI95% 2.53-217.96), Santa Rosa (OR: 19.33 CI 95% 1.81-206.73), and Lanchaco (OR:16.88 CI95% 1.71-166.21). The association with chromogenic bacteria was also significant in the three schools: Nicolás La Torre (OR:15.56 CI95% 1.70-142.05), Santa Rosa (OR:13.75 CI95% 1.31-143.85), and Lanchaco (OR:10.91 CI95% 1.14-104.81). Conclusions: in the schoolchildren from Pimentel, Salas, and Chiclayo there was an approximation between expected and found results, agreeing with other studies and antecedents.